Relationship Between Self-Esteem and the Tendency to Bully with Gender as a Moderator - Muhammad Abdulah (Program Studi Bimbingan Konseling Islam Fakultas Dakwah dan Komunikasi Institut Agama Islam Hamzanwadi NW Pancor, 2024)
Abstract Every individual has different levels of self-esteem, which can increase in both men and women, and at times can also decrease. Individuals with high self-esteem also tend to set high targets in everything and put in more effort to achieve the goals they want to reach. The purpose of this research is to elucidate and explain the relationship between self-esteem and the tendency to bully, with gender as a moderator. This research uses a quantitative approach with a correlational method. The measurement tools in this study are the self-esteem scale developed based on the aspects proposed by Rosenberg and the Bullying scale developed based on the aspects proposed by Ken Rigby. The sample size was 90 students. The sampling was conducted using the purposive sampling method. The research results show that the significance value of the self-esteem variable and the bullying variable is 0.047<0.05, indicating that the variables are correlated. The correlation level between the variables is 0.210, which means the correlation between the variables is weak. The conclusion can be interpreted that the higher the self-esteem, the lower the tendency for bullying behavior. Conversely, the lower the self-esteem, the higher the tendency for bullying behavior. Keywords: Self-Esteem, Bullying, Gender